Operability analysis on upscaled stirred tank for cellulose recovery from red meranti wood sawdust - Siti Noredyani, Abdul Rahman; Mimi Sakinah, Abdul Munaim (Universiti Malaysia Pahang, 2018)
Red Meranti wood sawdust (RMWS), a waste lignocellulosic biomass produced from forest activities, mostly from timber industries is the good source of cellulose. RMWS consists of three major components of polymer, which are cellulose, hemicellulose, and lignin. The huge amount of sawdust particles produced are typically combusted, relinquished or dumped into rivers, streams or drainages. Production of cellulose by chemical, physical and biological pretreatments processes of biomass has been proposed and studied in recent years to handle the environmental issues. Yet, just a few of them appear to be encouraging. This research aimed to bring the potentials scale up a plant from laboratory scale works to a 100l pilot scale of cellulose recovery process, in term of quality attributes to the overall system. The procedures involved in scaling-up the capacity by running the preliminary run using the upscaled stirred tank and identification of operability issues with proposed rectifications for new design features. Then, the rectified issues and the whole process are expected to run in new design of an intensified and improved batch reactor tank for commercialization later.